Comparing boys and girls in juvenile detention in Portugal: differences in psychopathic traits, criminal behaviors, and one-year recidivism - Pechorro, Pedro (Psychology, crime & law, 2023)
Gender is a critical explanatory variable among juvenile justice system-involved youth, with the literature showing differential protective and risk factors for serious delinquency among female and male youth. The aim of the current study is to examine gender differences in psychopathic and related traits, externalizing behaviors, and offense profiles among a sample of female (n = 76, M = 16.37 years, SD = 1.16) and male (n = 214, M = 16.40 years, SD = 1.30) youth incarcerated in Portugal. Results showed that boys tended to present significantly higher levels of psychopathic/callous–unemotional traits, conduct disorder, proactive aggression, and also lower levels of empathy. In terms of offense profiles, boys tended to present significantly higher levels of crime frequency, crime diversity, crime seriousness, days in detention, and general and violent one-year recidivism, and also lower ages of crime onset, first legal problem, and first detention. Findings support the notion that gender-informed services and supervisions are essential for understanding and intervening among justice-involved youth.